Comparison Of Risk Organ Distribution With Target Volume Size Variations Using Rapid ARC And IMRT Techniques For Case Of Lung Cancer - Eny Supriyaningsih; Guntur Winarno; Trisno Firmansyah (SANITAS: Jurnal Teknologi dan Seni Kesehatan, 2018)
This study aims to know how big the difference between dose distribution Rapid Arc and IMRT technique and gains on PTV dose 95%. This research is a descriptive qualitative research data obtained from Phantom to take three the size of the volume of the tumor is seen from the organs at risk of Medulla spinalis, heart, healthy and the lung from the results of the data processing and then analyzed the distribution of the received dose organs at risk. Data analysis is done using the Software eclipse. The result show received dose between flashes IMRT technique and Rapid arc technique on the size of the volume of cancer 250 cm3, 500 cm3, 750 cm3 on the part of the heart and the lungs, Rapid arc provides better radiation dose compared with IMRT but only the medulla spinalis get higher doses but still below the maximum dose organ and gains received on PTV dose 95% with the technique of Rapid Arc higher than IMRT technique.